Binder containing copolymer, negative electrode for secondary battery containing said binder, secondary battery containing said negative electrode, and method for polymerizing said copolymer

By developing a new copolymer as the negative electrode battery adhesive, the problems of reduced conductivity and deterioration of cycle performance caused by volume changes in silicon material in lithium-ion secondary batteries are solved, and higher adhesion and mechanical strength are achieved, improving the overall performance of the battery and the problems in the manufacturing process.

JP2025511973AActive Publication Date: 2025-04-16HANSOL CHEM
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024559697
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-11
Filing Date
2023-04-10
Publication Date
2025-04-16
Estimated Expiration
2043-04-10

Smart Images

  • Figure 2025511973000001
    Figure 2025511973000001
  • Figure 2025511973000002
    Figure 2025511973000002
  • Figure 2025511973000003
    Figure 2025511973000003
Patent Text Reader

Abstract

The present invention relates to poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol) (PVA-PAA-CEPVA), a method for producing the same, and an anode slurry, an anode, and a secondary battery containing the copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer that can be used as a binder, a method for producing the same, and a slurry, an electrode, and a secondary battery each containing the copolymer. [Background technology]

[0002] Lithium secondary batteries have a high energy density and are widely used in the electrical, electronic, communication and computer industrial fields. In addition to small lithium secondary batteries for portable electronic devices, their application fields are expanding to high-capacity secondary batteries for hybrid vehicles, electric vehicles and the like.

[0003] As the range of applications expands, lithium secondary batteries are required to have high capacity as well as long life characteristics. One method for increasing the capacity of lithium secondary batteries is to use an active material containing silicon atoms in the negative electrode.

[0004] When using active materials containing silicon atoms, which have a larger amount of lithium inserted / deintercalated compared to conventional carbon-based active materials, it is expected that the battery capacity will improve. However, silicon-containing active materials have a large volume change associated with the insertion / deintercalation of lithium, so the negative electrode active material layer expands and contracts significantly during charging and discharging.

[0005] As a result, the conductivity between the negative electrode active materials decreases, or the conductive path between the negative electrode active material and the current collector is interrupted, causing problems such as a deterioration in the cycle characteristics of the secondary battery.

[0006] However, the various binders that have been developed so far (PAA, PAA / CMC, Na-PAA, crosslinked PAA, alginate, PVA, SBR / CMC, etc.) have insufficient adhesive strength or make the electrodes excessively brittle and lack durability, so it is difficult to expect them to solve the volume expansion problem mentioned above.

[0007] That is, in the existing most widely used SBR / CMC aqueous binder system, CMC has low adhesive strength and high viscosity, making it difficult to add a large amount of it when producing a slurry, while SBR is a tacky adhesive type with excellent adhesive strength but has low mechanical strength and makes it difficult to suppress the expansion of silicon.

[0008] Due to the limitations of the existing adhesive system of SBR / CMC binders, binders for silicon active materials are being developed using linear polymers (PVA, PAA, etc.) that can achieve linear adhesion. However, linear polymers generate a large number of bubbles during slurry production, making it difficult to achieve a uniform coating and causing defects during electrode production. In addition, linear polymers can become entangled, reducing the efficiency of their original function as a binder, and the secondary bonding force between polymer chains is weak, making it difficult to suppress expansion.

[0009] To compensate for the low expansion suppression ability of linear polymers, crosslinked polymers that undergo crosslinking when the electrode is dried are sometimes used. However, crosslinked polymers have different degrees of crosslinking depending on the drying conditions, making them difficult to apply to the production process, and there is also a problem that the adhesive strength decreases after crosslinking.

[0010] Therefore, there is a demand for a binder that can solve these problems and improve the performance of secondary batteries. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Republic of Korea Patent Publication No. 10-2016-0024921 Summary of the Invention [Problem to be solved by the invention]

[0012] Therefore, the present invention aims to provide a copolymer that prevents entanglement to improve adhesion to a current collector, reduces linearity to suppress bubble formation, and improves coatability.

[0013] Another object of the present invention is to provide a copolymer that improves the adhesive strength between an active material and a current collector by grafting a functional group having excellent adhesive strength, maintains strong adhesive strength even when silicon expands, prevents the active material from being detached, and significantly reduces linearization of the binder to significantly reduce bubbles and coating defects that occur during the preparation of a slurry.

[0014] In addition, the present invention provides an electrode (particularly, an anode) having excellent performance by using the copolymer as a binder, and a secondary battery having excellent characteristics including the same.

[0015] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0016] One aspect of the present application is a polymerizable compound that includes a repeating unit represented by the following chemical formula 1: A copolymer is provided. [ka] In the above Chemical Formula 1, R1~R 13 are different or identical, and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 3 carbon atoms; R'1 is a cyano (-CN) group; R'2 is -OH, -OCOCH3 or -COOCH3; M is hydrogen or an alkali metal; 1≦l≦5% by weight, 10≦m≦85% by weight, and 10≦n≦85% by weight.

[0017] Another aspect of the present application is a method for producing a copolymer by copolymerizing a vinyl acetate monomer and an acrylate monomer; hydrolyzing the copolymer; and adding an acrylonitrile monomer to cyanoethylate the hydrolyzed copolymer. A method for producing a copolymer is provided.

[0018] Yet another aspect of the present application is a polymerizable composition comprising the copolymer, A negative electrode active material, An anode slurry is provided.

[0019] Yet another aspect of the present application is a battery comprising: a current collector; a negative electrode active material layer including the copolymer formed on the current collector, A negative electrode is provided.

[0020] Yet another aspect of the present application is a method for producing a method for manufacturing a semiconductor device comprising the steps of: The negative electrode is included. A secondary battery is provided. Effect of the Invention

[0021] The copolymer of the present invention improves adhesion to the current collector and maintains strong adhesion even when silicon expands, preventing detachment of the active material, and significantly reduces air bubbles and coating defects generated during preparation of electrode slurry.

[0022] In addition, the copolymer can be used as a binder to improve the performance of an electrode (particularly, a negative electrode) and a secondary battery including the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely examples of the present invention and do not define the scope of the invention.

[0024] Prior to this, the terms and words used in this specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with meanings and concepts that correspond to the technical ideas of the present invention, in accordance with the principle that an inventor can appropriately define the concepts of terms in order to explain his / her invention in the best possible way.

[0025] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.

[0026] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0027] In this specification, the terms "from" and "to" in the expressions "from a to b" and "a~b" that indicate numerical ranges are defined as ≧a and ≦b.

[0028] The copolymer according to one embodiment of the present application may include a repeating unit represented by the following Chemical Formula 1. [ka] In the above Chemical Formula 1, R1 to R 13 are different from each other or the same and each independently represent hydrogen or a linear or branched hydrocarbon having 1 to 3 carbon atoms; R'1 is a cyano (-CN) group; R'2 is -OH, -OCOCH3 or -COOCH3; M is hydrogen or an alkali metal; and 1≦l≦5 wt. %, 10≦m≦85 wt. %, and 10≦n≦85 wt.

[0029] The alkali metal may be at least one selected from the group consisting of lithium (Li), sodium (Na) and potassium (K).

[0030] In the copolymer, the monomer unit corresponding to (1) in Chemical Formula 1 may be a cyanoethylated vinyl alcohol-based monomer unit, the monomer unit corresponding to (2) in Chemical Formula 1 may be a vinyl alcohol monomer unit, and the monomer unit corresponding to (3) in Chemical Formula 1 may be an acrylic acid-based monomer unit.

[0031] For example, the acrylic acid-based monomer unit may be at least one selected from the group consisting of an acrylic acid salt, a methacrylic acid salt, an acrylic acid, and a methacrylic acid, but is not limited thereto.

[0032] When the copolymer is used as an electrode binder, the coating property and adhesive strength can be improved as the content of the monomer unit (1) of Formula 1 in the copolymer increases. However, if the content of the monomer unit (1) exceeds the range of the present application, the water solubility decreases, and the copolymer cannot be used as an aqueous binder.

[0033] In addition, when the copolymer is used as an electrode binder, the adhesive strength can be improved as the content of the monomer unit (2) of Formula 1 in the copolymer increases. However, if the content of the monomer unit (2) exceeds the range of the present application, the coating properties may be deteriorated.

[0034] Meanwhile, when the copolymer is used as an electrode binder, the battery performance can be improved as the content of the monomer unit (3) of Formula 1 in the copolymer increases. However, if the content of the monomer unit (3) exceeds the range of the present application, the adhesive strength and slurry stability may be reduced.

[0035] Also, the monomer units of the copolymer may consist only of the monomer units (1), (2) and (3) of the chemical formula 1.

[0036] In one embodiment, R to R in Formula 1 13 are different from each other or the same, and each may independently be any one selected from the group consisting of hydrogen, methyl, ethyl, n-propyl, and iso-propyl.

[0037] In one embodiment, the copolymer may be a random or block copolymer.

[0038] In one embodiment, the copolymer may have a number average molecular weight of 10,000 or more and 1,000,000 or less.

[0039] According to another aspect of the present disclosure, a method for producing a copolymer includes the steps of: copolymerizing a vinyl acetate monomer and an acrylate-based monomer to produce a copolymer; hydrolyzing the copolymerized copolymer; and adding an acrylonitrile-based monomer to cyanoethylate the hydrolyzed copolymer.

[0040] In the hydrolysis step, the vinyl acetate monomer unit and the acrylate monomer unit of the copolymer prepared by copolymerizing the vinyl acetate monomer and the acrylate monomer may be hydrolyzed into a vinyl alcohol monomer unit and an acrylic acid monomer unit, respectively.

[0041] In the hydrolysis step, an alkali metal hydroxide can be used, but is not limited to this.

[0042] Thereafter, a portion of the vinyl alcohol monomer units may be cyanoethylated by cyanoethylation.

[0043] In one embodiment, the acrylate monomer may be at least one selected from the group consisting of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, and ethylhexyl methacrylate, and the acrylonitrile monomer may be at least one selected from the group consisting of acrylonitrile and methacrylonitrile.

[0044] In one embodiment, a basic compound may be additionally added in the cyanoethylation step, and the basic compound may be any one or more selected from the group consisting of NaOH, KOH, and LiOH, but is not limited thereto.

[0045] According to yet another aspect of the present disclosure, a negative electrode slurry may include the copolymer and a negative electrode active material.

[0046] That is, the copolymer can be used as a binder for a negative electrode.

[0047] The peel strength between the negative electrode active material layer formed using the negative electrode slurry and the copper current collector may be 10 gf / cm or more, and preferably 11 gf / cm.

[0048] The negative electrode active material may be a compound containing one or more elements selected from the group consisting of a carbon-based material, silicon, an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, and a rare earth element, and may preferably be silicon or a compound containing silicon.

[0049] Examples of the carbonaceous material include, but are not limited to, artificial graphite, natural graphite, hard carbon, soft carbon, etc. The negative electrode active material containing silicon is not particularly limited as long as it is silicon or a compound containing silicon, but preferably Si, SiO x (0 < x < 2), Si-Y alloy (wherein Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element, or a combination thereof, and is not Si), and one or more selected from the group consisting of Si-C composites.

[0050] When the negative electrode active material containing silicon and another negative electrode active material are mixed and used as the negative electrode active material, the negative electrode active material containing silicon may be contained in an amount of 8% by weight or more based on the total weight of the negative electrode active material.

[0051] The negative electrode active material may be contained in an amount of 50 to 90% by weight, preferably 60 to 80% by weight, based on the total weight of the negative electrode active material layer.

[0052] When the content of the negative electrode active material is less than 50% by weight, the energy density decreases and a high-energy density battery cannot be manufactured. When the content exceeds 90% by weight, the contents of the conductive material and the binder decrease, the electrical conductivity decreases, and the adhesive force between the electrode active material layer and the current collector may decrease.

[0053] On the other hand, the copolymer binder of the present application may be contained in an amount of 1 to 20% by weight based on the total weight of the negative electrode slurry. If the copolymer is less than 1% by weight, the physical properties of the negative electrode may deteriorate and the negative electrode active material and the conductive material may fall off. If it exceeds 20% by weight, the ratio of the negative electrode active material to the conductive material may relatively decrease, the battery capacity may decrease, and the electrical conductivity of the negative electrode may decrease.

[0054] In addition, the negative electrode slurry may further include a polymer in addition to the copolymer of the present application. As the polymer, any polymer that can be dissolved or dispersed in a solvent for preparing the negative electrode slurry can be used, and in particular, a polymer that can be dissolved or dispersed in water can be used.

[0055] Specific examples of the polymer include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), metal polyacrylate (Metal-PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), chitosan, starch, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, hydroxypropyl cellulose, regenerated cellulose, and various copolymers thereof, but are not limited thereto.

[0056] A negative electrode according to still another aspect of the present application may include a current collector and a negative electrode active material layer including the copolymer of the present application formed on the current collector.

[0057] The negative electrode active material layer may further include a conductive material. The conductive material is used to further improve the conductivity of the negative electrode active material. The conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; polyphenylene derivatives, etc. may be used.

[0058] The conductive material may be contained in an amount of 5 to 30 wt %, preferably 15 to 25 wt %, based on the total weight of the negative electrode active material layer. If the conductive material is contained in an amount less than 5 wt %, the electrical conductivity of the negative electrode is reduced. If the conductive material is contained in an amount exceeding 30 wt %, the ratio of the silicon-based negative electrode active material to the binder is relatively reduced, resulting in a reduced battery capacity, and since the binder content must be increased to maintain the negative electrode active material layer, the negative electrode active material content is reduced, making it impossible to manufacture a battery with a high energy density.

[0059] In the negative electrode of the present application, the negative electrode active material layer contains the copolymer of the present application, so that volume expansion of the negative electrode active material that occurs during charging and discharging of the secondary battery can be suppressed, and the performance of the secondary battery can be improved.

[0060] The negative electrode can be manufactured by (a) preparing a negative electrode active material layer-forming composition containing a negative electrode active material and the copolymer of the present application, and (b) applying the negative electrode active material layer-forming composition onto a negative electrode current collector and drying the applied composition.

[0061] The composition for forming the negative electrode active material layer is prepared in a negative electrode slurry state, and the solvent for preparing the slurry state must be easy to dry, and most preferably, can dissolve the copolymer binder of the present application well and can maintain the negative electrode active material in a dispersed state without dissolving it.

[0062] The solvent according to the present application may be water or an organic solvent, and the organic solvent may be one or more selected from the group consisting of methylpyrrolidone, dimethylformamide, isopropyl alcohol, acetonitrile, methanol, ethanol, and tetrahydrofuran.

[0063] Preferably, water alone can be used as the solvent in the present application.

[0064] The negative electrode active material layer forming composition can be mixed by a conventional mixer such as a latex mixer, a high-speed shear mixer, or a homogenizer, by a conventional method.

[0065] The step (b) is a step of applying the composition for forming a negative electrode active material layer prepared in the step (a) onto a negative electrode current collector and then drying the composition to prepare a negative electrode for a lithium secondary battery.

[0066] Specifically, the negative electrode current collector may be selected from the group consisting of copper, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy. In addition, baked carbon, a non-conductive polymer surface-treated with a conductive material, or a conductive polymer may be used.

[0067] The composition for forming a negative electrode active material layer prepared in the step (a) is applied onto a negative electrode current collector, and the current collector can be coated with an appropriate thickness depending on the thickness to be formed, which can be appropriately selected preferably within the range of 10 to 300 μm.

[0068] At this time, a method for applying the slurry-like composition for forming a negative active material layer is not limited, and the composition may be prepared by, for example, a doctor blade coating, a dip coating, a gravure coating, a slit die coating, a spin coating, a comma coating, a bar coating, a reverse roll coating, a screen coating, a cap coating, or the like.

[0069] After coating, the coating is dried, and finally, a negative electrode for a secondary battery (particularly a lithium secondary battery) having a negative electrode active material layer formed thereon can be produced.

[0070] A battery according to still another aspect of the present application may include a current collector and a negative electrode in which the negative electrode active material layer is formed on the current collector.

[0071] The battery may be a secondary battery (particularly, a lithium secondary battery) including a positive electrode, the negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0072] The configurations of the positive electrode, separator and electrolyte of the lithium secondary battery are not particularly limited in the present invention and may be any known configuration in this field.

[0073] The positive electrode includes a positive electrode active material formed on a positive electrode current collector.

[0074] The positive electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery, and can be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In this case, the positive electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface to enhance adhesion to the positive electrode active material.

[0075] The positive electrode active material constituting the positive electrode active material layer can be any positive electrode active material used in the art. Specific examples of such positive electrode active materials include lithium metal; lithium cobalt oxides such as LiCoO2; Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxides such as Li2CuO2; vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; LiNi1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 - 0.3); LiMn 2-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 - 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); Li(Ni a Co b Mn c )O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1); sulfur or disulfide compounds; phosphates such as LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4; Fe2(MoO4)3, etc., but not limited to these only.

[0076] At this time, the positive electrode active material layer can additionally contain, in addition to the positive electrode active material, a binder, a conductive material, a filler, and other additives. The conductive material is the same as described above in the negative electrode for the lithium secondary battery.

[0077] Also, the binder includes, but is not limited to, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), chitosan, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene - propylene - diene polymer (EPDM), sulfonated - EPDM, styrene - butadiene rubber (SBR), fluororubber, and various copolymers thereof.

[0078] The separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in electrochemical devices, such as, but not limited to, a polyolefin-based porous membrane or nonwoven fabric.

[0079] The separation membrane may be a porous substrate made of any one selected from the group consisting of polyethylene, polypropylene, polybutylene, polypentene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate, or a mixture of two or more of these.

[0080] The electrolyte of the lithium secondary battery is a non-aqueous electrolyte containing a lithium salt, and is composed of a lithium salt and a solvent. As the solvent, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used.

[0081] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiC4BO8, LiCF3CO2, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2F)2, LiN(SO2C2F5)2, LiC4F9SO3, LiC(CF3SO2)3, (CF3SO2)·2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, and lithium 4-phenylborate imide can be used.

[0082] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydroxyfuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, and ethyl propionate.

[0083] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing secondary dissociation groups.

[0084] Examples of the inorganic solid electrolyte that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.

[0085] The non-aqueous electrolyte may further contain other additives for the purpose of improving charge / discharge characteristics, flame retardancy, etc. Examples of the additives include pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, fluoroethylene carbonate (FEC), propene sultone (PRS), vinylene carbonate (VC), etc.

[0086] The lithium secondary battery according to the present invention can be manufactured by lamination stacking of separators and electrodes and folding processes in addition to the general winding process, and the battery case may be cylindrical, square, pouch-shaped, or coin-shaped. EXAMPLES

[0087] The present application will be described in more detail below using examples, but the present application is not limited thereto.

[0088] [Example 1] 944 g of distilled water and 9 g of alkyldiphenyloxide disulfonate were placed in a reactor, and the mixture was stirred for 1 hour while blowing in nitrogen.

[0089] Thereafter, 1.29g of potassium persulfate was added, and the temperature of the reactor was raised to 60°C. Then, 115g of vinyl acetate and 312g of ethyl acrylate were added dropwise for 3 hours, and the reaction was terminated by maintaining the temperature for 2 hours to obtain 30% by weight of vinyl acetate-ethyl acrylate copolymer (poly(vinylacetate-co-ethylacrylate), PVAc-PEA).

[0090] A reactor was charged with 150 g of ethanol to dissolve 100 g of 30 wt % PVAc-PEA, and then 27 g of a basic compound was added and hydrolysis was carried out with stirring at 60° C. for 4 hours.

[0091] After completion of hydrolysis, the precipitated hydrolyzate was dissolved in distilled water and heated to 80°C to obtain 5% by weight of poly(vinyl alcohol-co-acrylic acid) (PVA-PAA).

[0092] 1 part by weight of 5% PVA-PAA was added to a reactor, 0.1 part by weight of a basic compound and 0.5 part by weight of acrylonitrile were added for a certain period of time, and then cyanoethylation was carried out while stirring at 40°C for 2 hours.

[0093] After the reaction was completed, an aqueous solution of poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol) (PVA-PAA-CEPVA) was obtained.

[0094] [Example 2] 944 g of distilled water and 9 g of alkyldiphenyloxide disulfonate were placed in a reactor, and the mixture was stirred for 1 hour while blowing in nitrogen.

[0095] Thereafter, 1.29g of potassium persulfate was added, and the temperature of the reactor was raised to 60°C. Then, 197g of vinyl acetate and 229g of ethyl acrylate were added dropwise for 3 hours, and the reaction was terminated by maintaining the temperature for 2 hours to obtain 30% by weight of vinyl acetate-ethyl acrylate copolymer (poly(vinylacetate-co-ethylacrylate), PVAc-PEA).

[0096] A reactor was charged with 150 g of ethanol to dissolve 100 g of 30 wt % PVAc-PEA, and then 27 g of a basic compound was added and hydrolysis was carried out with stirring at 60° C. for 4 hours.

[0097] After completion of hydrolysis, the precipitated hydrolyzate was dissolved in distilled water and heated to 80°C to obtain 5% by weight of poly(vinyl alcohol-co-acrylic acid) (PVA-PAA).

[0098] 1 part by weight of 5% PVA-PAA was added to a reactor, 0.1 part by weight of a basic compound and 0.5 part by weight of acrylonitrile were added for a certain period of time, and then cyanoethylation was carried out while stirring at 40°C for 2 hours.

[0099] After the reaction was completed, an aqueous solution of poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol) (PVA-PAA-CEPVA) was obtained.

[0100] [Example 3] Vinyl acetate (vinylacetate) 285g and ethyl acrylate (ethylacrylate) 142g were reacted instead of vinyl acetate (vinylacetate) 197g and ethyl acrylate (ethylacrylate) 229g to obtain 30 wt% vinyl acetate-ethyl acrylate copolymer (poly(vinylacetate-co-ethylacrylate), PVAc-PEA), except that the reaction was carried out in the same manner as in Example 2 to produce vinyl alcohol-acrylic acid-cyanoethylated vinyl alcohol copolymer (poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA).

[0101] [Example 4] Instead of 197g of vinyl acetate and 229g of ethyl acrylate, 115g of vinyl acetate and 312g of ethyl acrylate were reacted to obtain 30% by weight of vinyl acetate-ethyl acrylate copolymer (poly(vinylacetate-co-ethylacrylate), PVAc-PEA), and the reaction was carried out in the same manner as in Example 2, except that 0.3 parts by weight of acrylonitrile was used instead of 0.5 parts by weight of acrylonitrile in the cyanoethylation step, to produce poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA.

[0102] [Comparative Example 1] 944 g of distilled water and 9 g of alkyldiphenyloxide disulfonate were placed in a reactor, and the mixture was stirred for 1 hour while blowing in nitrogen.

[0103] Then, 1.29g of potassium persulfate was added and the temperature of the reactor was raised to 60°C. Then, 427g of vinylacetate was added dropwise over 3 hours, and the reaction was terminated by maintaining the temperature for 2 hours to obtain 30% by weight of polyvinyl acetate (PVAc).

[0104] A reactor was charged with 150 g of ethanol to dissolve 100 g of 30 wt % PVAc, and then 27 g of a basic compound was added and hydrolysis was carried out with stirring at 60° C. for 4 hours.

[0105] After completion of the hydrolysis, the precipitated hydrolyzate was dissolved in distilled water and heated to 80° C. to obtain a 5% by weight vinyl alcohol polymer (polyvinyl alcohol, PVA).

[0106] 1 part by weight of 5% PVA was added to a reactor, 0.1 part by weight of a basic compound and 0.5 part by weight of acrylonitrile were added for a certain period of time, and then cyanoethylation was carried out while stirring at 40° C. for 2 hours.

[0107] After the reaction was completed, an aqueous solution of poly(vinyl alcohol-co-cyanoethylated vinyl alcohol) (PVA-CEPVA) was obtained.

[0108] [Comparative Example 2] 944 g of distilled water and 9 g of alkyldiphenyloxide disulfonate were placed in a reactor, and the mixture was stirred for 1 hour while blowing in nitrogen.

[0109] Then, 1.29g of potassium persulfate was added, and the temperature of the reactor was raised to 60°C. Then, 427g of ethylacrylate was added dropwise for 3 hours, and the reaction was terminated by maintaining the temperature for 2 hours to obtain 30% by weight of ethyl acrylate polymer (polyethyl acrylate, PEA).

[0110] A reactor was charged with 150 g of ethanol to dissolve 100 g of 30 wt % PEA, and then 27 g of a basic compound was added and hydrolysis was carried out at 60° C. for 4 hours with stirring.

[0111] After completion of the hydrolysis, the precipitated hydrolyzate was dissolved in distilled water and heated to 80° C. to obtain 5% by weight of an acrylic acid polymer (polyacrylic acid, PAA).

[0112] [Comparative Example 3] The reaction was carried out in the same manner as in Example 2, except that the cyanoethylation step was not carried out, to obtain 5% by weight of poly(vinyl alcohol-co-acrylic acid), PVA-PAA.

[0113] [Comparative Example 4] The same reaction as in Example 4 was carried out, except that 1.1 parts by weight of acrylonitrile was used instead of 0.3 parts by weight of acrylonitrile in the cyanoethylation step, to prepare poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA.

[0114] The weight percentage and water solubility of each monomer unit of the copolymers produced in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1 below.

[0115] [Table 1]

[0116] In Table 1, VA represents a vinyl alcohol monomer unit, AA represents an acrylic acid monomer unit, and CEVA represents a cyanoethylated vinyl alcohol monomer unit. In terms of water solubility, "O" indicates that the compound dissolves in water, and "X" indicates that the compound does not dissolve in water and precipitates.

[0117] [Production Example 1] Production of negative electrode A negative electrode slurry was prepared by mixing 89 g of artificial graphite as an electrode active material, 8 g of SiOx, 3.2 g of carbon nanotubes, 3 g of a binder containing the copolymers prepared in Examples 1 to 4 and Comparative Examples 1 to 4, and distilled water.

[0118] The prepared negative electrode slurry was uniformly coated on a copper current collector, dried at 110° C., and the resulting mixture was rolled and heated in a vacuum oven at 110° C. for 4 hours or more to prepare a negative electrode.

[0119] [Production Example 2] Production of lithium secondary batteries A non-aqueous electrolyte solution containing a lithium salt was used as an electrolyte, and a polyolefin separator was interposed between the positive electrode and the negative electrode prepared according to Preparation Example 1, and a lithium secondary battery was manufactured in either a pouch or coin cell type.

[0120] The non-aqueous electrolyte used was a solution of LiPF6 electrolyte at a concentration of 1M in a solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate were mixed in a volume ratio of 3:5:2.

[0121] [Evaluation Example 1] Evaluation of coating properties of negative electrode slurry While negative electrodes were produced by Production Example 1 using the copolymers of Examples 1 to 4 and Comparative Examples 1 to 4, it was visually observed whether the negative electrode slurry used was uniformly applied to the copper current collector.

[0122] In addition, the presence or absence of bubbles in the negative electrode slurry applied to the copper current collector was visually observed.

[0123] [Evaluation Example 2] Evaluation of adhesive strength of copolymer Negative electrodes were produced by Production Example 1 using the copolymers of Examples 1 to 4 and Comparative Examples 1 to 3, and the copper current collector of the produced negative electrode and the negative electrode slurry layer formed on the copper current collector were peeled off at an angle of 180° using a Universal Testing Machine (UTM) to measure the adhesive strength.

[0124] [Evaluation Example 3] Measurement of battery characteristics A lithium secondary battery was produced in accordance with Production Example 2 using the copolymers of Examples 1 to 4 and Comparative Examples 1 to 3 and the negative electrode produced in Production Example 1.

[0125] Thereafter, the fabricated lithium secondary battery was repeatedly charged and discharged at 1C for 60 cycles.

[0126] The coating properties, adhesive strength and battery characteristics (capacity retention rate) measured in Evaluation Examples 1, 2 and 3 are shown in Table 2 below.

[0127] [Table 2]

[0128] In Table 2, "good" indicates that the coating was uniformly formed on the current collector and there was no problem with the coating, and "deteriorated" indicates that stripes were formed on the current collector during coating or that air bubbles were generated and the coating was not uniform.

[0129] Additionally, an "O" next to the air bubbles indicates that air bubbles were observed, and an "X" indicates that air bubbles were not observed.

[0130] In the case of the negative electrode using the vinyl alcohol-cyanoethylated vinyl alcohol copolymer (poly(vinyl alcohol-co-cyanoethylated vinyl alcohol), PVA-CEPVA) of Comparative Example 1 as a binder, the coating property was decreased, air bubbles were observed, and it was confirmed that the adhesive strength was also decreased compared to the negative electrodes using the vinyl alcohol-acrylic acid-cyanoethylated vinyl alcohol copolymer (poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA) of Examples 1 to 4 as a binder.

[0131] In addition, it was confirmed that the negative electrode using the acrylic acid polymer (polyacrylic acid, PAA) of Comparative Example 2 as a binder had a lower coating property and adhesive strength than the negative electrodes using the vinyl alcohol-acrylic acid-cyanoethylated vinyl alcohol copolymers (poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA) of Examples 1 to 4 as a binder.

[0132] In addition, it was confirmed that the adhesive strength of the negative electrode using the vinyl alcohol-acrylic acid copolymer (poly(vinyl alcohol-co-acrylic acid), PVA-PAA) of Comparative Example 3 as a binder was lower than that of the negative electrodes using the vinyl alcohol-acrylic acid-cyanoethylated vinyl alcohol copolymers (poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol), PVA-PAA-CEPVA) of Examples 1 to 4 as a binder.

[0133] On the other hand, the poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol) copolymer (PVA-PAA-CEPVA) in which the content of cyanoethylated vinyl alcohol monomer units was increased to 10% by weight in Comparative Example 4 was not only insoluble in water, but also unable to form a coating on the current collector, making it impossible to manufacture an electrode and a battery.

[0134] In addition, it can be confirmed that the lithium secondary batteries using the negative electrodes in which the poly(vinyl alcohol-co-acrylic acid-co-cyanoethylated vinyl alcohol) copolymers of Examples 1 to 4 are used as binders have a better capacity retention rate per cycle than the lithium secondary batteries using the negative electrodes in which the copolymers of Comparative Examples 1 to 3 are used as binders.

[0135] As a result, it was confirmed that the copolymer binders of Examples 1 to 4 of the present application provide better coating properties and adhesive strength during electrode preparation compared to the copolymer or polymer binders of Comparative Examples 1 to 4, thereby making it possible to prepare a lithium secondary battery with excellent capacity retention per cycle.

[0136] The scope of the present invention is defined by the following claims rather than the above detailed description, and all modifications and variations derived from the meaning and scope of the claims and their equivalent concepts should be interpreted as being included in the scope of the present invention.

[0137] The copolymer of the present invention improves adhesion to the current collector and maintains strong adhesion even when silicon expands, preventing detachment of the active material, and significantly reduces air bubbles and coating defects generated during preparation of electrode slurry.

[0138] In addition, the copolymer can be used as a binder to improve the performance of an electrode (particularly, a negative electrode) and a secondary battery including the same.

Claims

1. The repeating unit represented by the following chemical formula 1 is included: Copolymer. 【Chemistry 1】 In the above Chemical Formula 1, R 1 ~R 13 are different or the same and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 3 carbon atoms; R' 1 is a cyano (-CN) group, R' 2 is -OH, -OCOCH 3 or -COOCH 3 and M is hydrogen or an alkali metal; 1≦l≦5% by weight, 10≦m≦85% by weight, and 10≦n≦85% by weight.

2. R of Formula 1 1 ~R 13 are different from each other or the same, and each is independently any one selected from the group consisting of hydrogen, methyl, ethyl, n-propyl, and iso-propyl; The copolymer of claim 1.

3. The copolymer is a random or block copolymer. The copolymer of claim 1.

4. The number average molecular weight of the copolymer is 10,000 or more and 1,000,000 or less. The copolymer of claim 1.

5. A step of copolymerizing a vinyl acetate monomer and an acrylate monomer to prepare a copolymer; hydrolyzing the copolymer; and adding an acrylonitrile monomer to cyanoethylate the hydrolyzed copolymer. Method for producing copolymers.

6. The acrylate monomer is at least one selected from the group consisting of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, and ethylhexyl methacrylate; The acrylonitrile monomer is at least one selected from the group consisting of acrylonitrile and methacrylonitrile; A method for producing the copolymer according to claim 5.

7. In the cyanoethylation step, a basic compound is additionally added; A method for producing the copolymer according to claim 5.

8. The copolymer according to any one of claims 1 to 4, A negative electrode active material, Anode slurry.

9. A current collector; a negative electrode active material layer formed on the current collector, the negative electrode active material layer comprising the copolymer according to any one of claims 1 to 4; Negative electrode.

10. The negative electrode according to claim 9, Secondary battery.

Citation Information

Patent Citations

  • Laminated porous film, separator for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2015151445A

  • Lithium secondary battery and method for manufacturing the same

    JP2015506550A

  • Cyanoethyl group-containing polymer and method for producing same

    JP2019509383A

  • Binder for secondary battery comprising copolymer of vinyl acetate or vinyl alcohol

    KR1020090019630A

  • Recyclable delivery Pack

    KR102440997B1